An extrinsic Fabry–Pérot interference fiber sensor for ultrasonic detection of partial discharge - Zhang, Ximin; Qian, Sen; Liu, Huixin; Chen, Chuan; Deng, Chuanlu; Hu, Chengyong; Huang, Yi (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
An ultrasonic sensor based on extrinsic Fabry–Pérot interference (EFPI) has been designed and demonstrated to detect the ultrasonic wave signal. The sensitivity and natural frequency of fiber Fabry–Pérot (F-P) sensor with different structure parameter have been simulated by COMSOL. The simulation results illustrate that the sensitivity is up to 1.737 nm/kPa and the natural frequency is 2.1 MHz, when the silica diaphragm thickness is 2 μm, the radius is 90 μm, and the cavity length is 18 μm. The most suitable parameters have been selected and the F-P sensor has been fabricated. When the ultrasonic signals with the frequencies of 40 kHz and 1.2 MHz are respectively applied to the sensor, the frequencies detected by the EFPI ultrasonic sensor are 39 kHz and 1.21 MHz based on a partial discharge detection experiment for the designed demodulation system. The experimental results show that the sensor can accurately detect ultrasonic signals. As an excellent platform for ultrasonic signal sensing, this EFPI ultrasonic sensing system has great potential applications in partial discharge detection field.
Optica Applicata, Vol. 53, 2023, nr 2, s. 199-211
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; extrinsic Fabry–Pérot interference; fiber sensor; partial discharge; sensitivity; frequency